Political Ecotourism: Lake Sebedang Tourism Object Development Strategy Through Community-Based Tourism - Fuzy Firda Zhan (MultiTech Publisher, 2024)
West Kalimantan Province is blessed with a wealth of tourism potential, including Lake Sebedang in Sambas Regency. However, there are complex problems from the political side of ecotourism in it. This research was conducted to analyze the strategy for developing the Sebedang Lake tourist attraction through the concept of community-based tourism from an ecotourism political perspective. The method used is a descriptive qualitative. The data in this research were obtained from interviews and documentation studies. Through this research, a strategy formulation was produced that can support increased development of the Sebedang Lake tourist attraction in harmony with environmental sustainability through community-based tourism, namely the need for synergy between stakeholders and the community as the main actors.